PENGARUH KELOMPOK ACUAN TERHADAP KESADARAN DAN KONSUMSI BERAS MERAH (ORIZA NIVARA) - Yuliati, Lilik Noor; Retnaningsih, Retnaningsih; Aprilia, Dini (Jurnal Ilmu Keluarga dan Konsumen, 2012)
Several years lately, brown rice (Oryza nivara) consumption has been popular as the part of healthy life style. This research aimed to analyze the reference group’s influence towards awareness and consumption of brown rice in Bogor. This research involved 130 consumer who’s choosed by snowball method. This research revealed that reference group was influenced by the motive of consumption. It also significantly related to consumer’s age. The awareness had a relationship with education level and media, but only education level that gave significant influence towards awareness. Reference group’s strength also gave an influence, that is the increasing in reference group’s strength will lessen the awareness. This can be happen because there was information overload perceived by consumer. The brown rice consumption significantly related to the education level, family income (socio-economic status), and awareness. However, only the awareness that was significantly influenced the consumption of brown rice.